2009
DOI: 10.1109/ted.2009.2021720
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of Nanowire FETs in a Partially Ballistic or Dissipative Transport Regime

Abstract: The intermediate transport regime in nanoscale transistors between the fully ballistic case and the quasiequilibrium case described by the drift-diffusion model is still an open modeling issue. Analytical approaches to the problem have been proposed, based on the introduction of a backscattering coefficient, or numerical approaches consisting in the Monte Carlo solution of the Boltzmann transport equation or in the introduction of dissipation in quantum transport descriptions.In this paper we propose a very si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The numerical solution of the complete chain of N elements: 2 of the boundary kind and N − 2 of internal kind, will be addressed as the B(N) model. Now we note that for the internal part of the chain the analysis developed in [24] applies. In particular it has been shown that the current in an ohmic-contact ballistic chain of N elements, after a linearization procedure, can be arranged in a to a drift-diffusion-like form (that we refer as the DD(N) model) in which the current is calculated through the formula…”
Section: Sb Transistors In Intermediate Transport Regimementioning
confidence: 99%
See 1 more Smart Citation
“…The numerical solution of the complete chain of N elements: 2 of the boundary kind and N − 2 of internal kind, will be addressed as the B(N) model. Now we note that for the internal part of the chain the analysis developed in [24] applies. In particular it has been shown that the current in an ohmic-contact ballistic chain of N elements, after a linearization procedure, can be arranged in a to a drift-diffusion-like form (that we refer as the DD(N) model) in which the current is calculated through the formula…”
Section: Sb Transistors In Intermediate Transport Regimementioning
confidence: 99%
“…The linearized DD model (35) has also the advantage of dealing with non integer N = L/ℓ, and is therefore more flexible than the ballistic chain itself. As noted in [24], (35) can be rearranged in a local form, analogous to a DD equation…”
Section: Sb Transistors In Intermediate Transport Regimementioning
confidence: 99%
“…Some attempts towards this definition have been made previously [24,25]. Here, we have followed [25] and dealt with this issue by defining an ideal square (depicted in dashed lines in Fig. 6) with its sides parallel to the semiconductor-insulator interfaces.…”
Section: Inversion Charge Centroid Calculationmentioning
confidence: 99%
“…First, the semiconductor-insulator interface is not isopotential, making Eq. (9) an approximate expression [8,19,25]. Moreover, there are no closed analytical expressions either for C ins or for C ch .…”
Section: Gate-to-channel Capacitance Modelingmentioning
confidence: 99%
“…Another capacitance based analytic model of ballistic silicon nanowire is also given in (Wang, 2005). Working out an analytic model covering ballistic and diffusive transport and also realizing transition between both (Michetti et al,2009) is another challenging task. With the above mentioned preliminary compact model for silicon nanowire MOSFET implemented into circuit simulations by Verilog-A, several representative logic circuits are simulated (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%